Factors Playing a Role in Sleep Disorders in Post-COVID-19 (Coronavirus Disease) Patients at the Neurology Polyclinic of Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Hasnawi Haddani; Handayani, Sri; Yunni Diansari; Afriani; Mukhlisa; Rifka Humaida; Citra Ananta Avis (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Sleep disorders are one of the symptoms frequently reported in post-COVID-19 patients. This study aims to identify factors that play a role in sleep disorders in post-COVID-19 patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This research was conducted in an analytical observational manner with a cross-sectional design. Data was collected from 100 post-COVID-19 patients treated at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Data were analyzed using the logistic regression test. Results: Factors that play a role in sleep disorders in post-COVID-19 patients are depressive symptoms (OR=2.5; 95%CI: 1.3-4.8); Anxiety symptoms (OR=3.1; 95%CI: 1.6-5.9); Stress level (OR=2.2; 95%CI: 1.1-4.3); Sleep quality before COVID-19 (OR=2.0; 95%CI: 1.0-3.9). Conclusion: Symptoms of depression, anxiety, stress, and sleep quality before COVID-19 are factors that play a role in sleep disorders in post-COVID-19 patients.